Early life nutrition, glycemic and anthropometric profiles of children exposed to gestational diabetes mellitus in utero. (March 2018) - Dugas, Camille; Kearney, Michèle; Mercier, Roxanne; Perron, Julie; Tchernof, André; Marc, Isabelle; Weisnagel, S. John; Robitaille, Julie
Highlights: This study showed that prolonged infant feeding with breast milk, at least >8 months, is associated with lower A1C levels in children exposed to GDM. Neither exclusive breastfeeding duration nor the timing of solid food introduction was associated with glycemic or anthropometric profile of children. These results suggest that the impact of in utero exposure to GDM can be partly attenuated by prolonged breastfeeding duration during early life.